SISTEM INFORMASI PENGENDALIAN ASSET KENDARAAN DI PERUSAHAAN TRANSPORTASI - Donny Sanjaya; Hafizh Abdurachman; Austin Arif Wicaksono; Fajar Masya (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
The process of controlling assets in a company is often constrained because of the lack of tools and systems. To facilitate the control of assets owned by the company in reducing the budget, a web-based application was made with the name "REMINDsset" that can be accessed by web browser any. This application is based on the needs of the company to check the condition of the assets owned by the company. This application is expected to be able to help company owners to manage assets, especially in vehicle parts. The company can automatically be notified of the condition of vehicles owned by the company, the company can also periodically check